2013
DOI: 10.1186/2191-0855-3-32
|View full text |Cite
|
Sign up to set email alerts
|

Psychrotrophic yeast Yarrowia lipolytica NCYC 789 mediates the synthesis of antimicrobial silver nanoparticles via cell-associated melanin

Abstract: A psychrotrophic marine strain of the ascomycetous yeast Yarrowia lipolytica (NCYC 789) synthesized silver nanoparticles (AgNPs) in a cell-associated manner. These nanostructures were characterized by UV-Visible spectroscopy and scanning electron microscope-energy dispersive spectrometer (SEM-EDS) analysis. The brown pigment (melanin) involved in metal-interactions was obtained from the cells. This extracted pigment also mediated the synthesis of silver nanoparticles that were characterized by a variety of ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(50 citation statements)
references
References 49 publications
1
49
0
Order By: Relevance
“…We have got very similar AFM results for the characterization of the silver and ZnO nanoparticles observed in some previous studies, respectively [30,32]. We have got similar functional groups through FTIR analysis in some previous studies for the confirmation of AGNPs and ZnONPs, respectively [25,33]. On the other hand, in a recent study, they have observed DPPH scavenging activity of synthesized silver nanoparticles extracted from leaf samples and they have found highest activity as 4.30 µg/ml [34].…”
Section: Discussionsupporting
confidence: 60%
“…We have got very similar AFM results for the characterization of the silver and ZnO nanoparticles observed in some previous studies, respectively [30,32]. We have got similar functional groups through FTIR analysis in some previous studies for the confirmation of AGNPs and ZnONPs, respectively [25,33]. On the other hand, in a recent study, they have observed DPPH scavenging activity of synthesized silver nanoparticles extracted from leaf samples and they have found highest activity as 4.30 µg/ml [34].…”
Section: Discussionsupporting
confidence: 60%
“…However, there are fewer reports on their use for mediating the AgNPs production in comparison to those reporting on the use of bacterial extracts. [36][37][38][39] Pigmented yeasts R. glutinis and R. mucilaginosa isolated in this study were observed to be able to reduce Ag + and to produce homogenous colloidal AgNPs from AgNO 3 (1.0 mmol L -1 ) when this salt is dissolved in their fungal extract. The nanoparticle formation after 168 h was confirmed by its plasmon absorption band, manifesting at a wide range of the UV-Vis absorption spectrum (see Figure S1 in the SI file).…”
Section: Characterization Of Synthetic and Biogenic Agnpsmentioning
confidence: 70%
“…These compounds improve the potential for these strains to produce metal nanoparticles as prominent building blocks in nanotechnology (Pimprikar et al, 2009). Some potential strains of Y. lipolytica may be used to generate elemental metal nanoparticles (Agnihotri et al, 2009;Apte et al, 2013). This field of research is still in its infancy.…”
Section: Production Of Nanoproductsmentioning
confidence: 99%